Original article (Folia Neuropathologica, 2011)

(untitled) - Castejón, Orlando J.
In human traumatic brain oedema pericytes exhibit remarkable oedematous changes, increased vacuolar and vesicular transport, transient transpericytal channels, and tubular structures demonstrating pericyte brain barrier dysfunction. They show nuclear invaginations, actin and myosin-like filaments, and coupled interaction with endothelial cells through the macula occludens. Some pericytes display hypertrophic and necrotic changes, and phagocytic capacity. Hypertrophic pericytes induce basement membrane splitting. Degenerated pericytes exhibit lacunar enlargement of endoplasmic reticulum, dense osmiophilic bodies, glycogen granules, vacuolization, oedematous Golgi apparatus, and pleomorphic mitochondria. Certain micropinocytotic vesicles are orientated to the Golgi complex and multivesicular bodies, suggesting that pericytes play some role in oedema resolution.